Blends of biodegradable poly(butylene adipate-co-terephthalate) with poly(hydroxi amino ether) for packaging applications: Miscibility, rheology and transport properties. (August 2018) - Sangroniz, Ainara; Sangroniz, Leire; Aranburu, Nora; Fernández, Mercedes; Santamaria, Antxon; Iriarte, Marian; Etxeberria, Agustin
Graphical abstract: Highlights: Poly(butylene adipate-co-terephthalate)/poly(hydroxi amino ether) blends have been prepared. Immiscible blends are obtained with very good compatibility. The morphology and hydrogen bonds determine the rheological properties. The barrier character of poly(butylene adipate-co-terephthalate) is greatly improved. Abstract: The improvement of the properties of biodegradable poly(butylene adipate-co-terephthalate) (PBAT) through the addition of poly(hydroxi amino ether) (PHAE) is investigated. Analysis by means of DSC, DMTA, FTIR and TEM reveals that blends are partially miscible, with finely dispersed droplet/matrix morphology. Besides of morphology, hydrogen bonds between both, hydroxyl groups and tertiary amines in neat poly(hydroxi amino ether), and with carbonyl groups of poly(butylene adipate-co-terephthalate) in the blends, work out the linear viscoelastic properties and the time relaxation spectrum. Blends rich in poly(hydroxi amino ether) show the highest relaxation times and consequent strain hardening behaviour, which facilitates film elaboration for packaging. Permeability to water vapour, limonene and carbon dioxide is measured obtaining a great reduction on PBAT permeability with the addition of poly(hydroxi amino ether), specially for carbon dioxide. The mechanical properties of the blends are similar to the polymer that forms the matrix. Overall, this work aims to shed light on the effect of a second component on the properties of a biodegradable polymer in order to design suitable materials for packaging applications.